Displaying a negative stance by questioning meaning: the Italian format Che cosa vuol dire X? ("What does X mean?") - De Stefani, Elwys (Interactional linguistics, 2024)
Abstract Speakers of Italian have at their disposal a variety of phrasal and clausal resources for questioning meaning, among which is the format che cosa vuol dire X? (‘what does X mean?’). Likewise, recent studies on English and German about similar resources have shown that speakers use them to identify a meaning problem. This contribution takes a step further, by showing that the ‘what does X mean?’ format allows speakers to accomplish a variety of actions. These may be related to (a) the negotiation of understanding, and (b) the display of a negative stance. In many occurrences, the interactants display clear orientation to either a problem of understanding or a commonly shared negative stance. However, in sensitive environments (such as conflictual discussions), the resource allows speakers to (c) frame their negative stance as a problem of understanding, thereby resisting escalation of the conflict. The ‘what does X mean?’ format may or may not be produced with concomitant embodied behaviour. When the format is used to problematise understanding, no specific embodied conduct is observed. Yet, when it is used to display a negative stance, speakers may be seen to perform the grappolo gesture.
Online veröffentlicht am 12. Januar 2024
Gesehen am 15.01.2025